Laparoscopic nephrectomy in live donor - Mitre,Anuar I. (2004)
OBJECTIVE: To present the initial experience of videolaparoscopic nephrectomy in live renal donor. MATERIALS AND METHODS: In the period from April 2000 to August 2003, 50 left nephrectomies in live donor were performed by videolaparoscopy for transplantation. Twenty-eight patients were male (56%) and 22 female (44%). Mean age was 37.2 years, and the mean body mass index (BMI) was 27.1 kg/m². RESULTS: Mean surgical time was 179.5 minutes, and warm ischemia time of the graft was 3.79 minutes. The mean estimated bleeding was 141 mL. There was no need of blood transfusion or conversion to open surgery. In 42 cases (84%), the vascular portion of the graft was considered good by the recipient's surgical team and in all cases, the ureter was considered of proper size, though in one of them (2%) its vascularization was considered improper. The transplanted kidneys produced urine still in the surgical room in 46 of the 50 transplantations considered. In only 2 cases opioid was required for analgesia. In average, 3.1 doses of dipyrone were used for each patient during hospital stay, and hospital discharge occurred, in average, after 3.2 days post-operatively. Two patients required re-operations and one of them evolved to death. CONCLUSIONS: The laparoscopic nephrectomy in live donor for renal transplantation is an alternative to conventional open surgery. In relation to the graft, no alteration, either anatomic or functional, was detected. Though there is already a large documentation in the international literature regarding this procedure, in our setting a prospective randomized study with the usual surgical study is still necessary in order to prove the advantages and disadvantages of the method.